Transmission of SARS-CoV-2 Infection by Children: A Study of Contacts of Index Paediatric Cases in India - Gupta, Nitin (J Trop Pediatr, 2020)
The susceptibility of children to coronavirus disease-19 (COVID-19) and transmission of COVID-19 from children to others is a relatively unexplored area. The aim of this study was to understand the transmission dynamics of Severe Acute Respiratory Syndrome Coronavirus 2 in children. This was a retrospective observational study where a total of 19 paediatric index cases (including a set of twins) with COVID-19 and 42 primary contacts (adults—36, paediatric—6) from the immediate family members were included. All the index cases and four of the five positive contacts were asymptomatic. Despite adults staying with positive children in the same vehicle, same room in the quarantine centre and the same ward, only four of the parents became positive.